2017
DOI: 10.1007/s12079-017-0428-0
|View full text |Cite
|
Sign up to set email alerts
|

A function-blocking CD47 antibody modulates extracellular vesicle-mediated intercellular signaling between breast carcinoma cells and endothelial cells

Abstract: Tumor cells release extracellular vesicles (EVs) into the tumor microenvironment that may facilitate malignant progression and metastasis. Breast carcinoma EVs express high levels of the thrombospondin-1 and signal regulatory protein-α receptor CD47, which is the target of several experimental therapeutics currently in clinical trials. We analyzed changes in gene expression and function in human umbilical vein endothelial cells (HUVEC) induced by treatment with EVs derived from breast carcinoma cells and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 80 publications
(103 reference statements)
3
26
0
Order By: Relevance
“…All RNA samples were subjected to treatment with DNAse-1 prior to first strand cDNA synthesis according to the manufacturer's instructions (Thermo Fisher Scientific). Real-time PCR was performed using SYBR Green detection on a Bio-Rad CFX instrument as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
“…All RNA samples were subjected to treatment with DNAse-1 prior to first strand cDNA synthesis according to the manufacturer's instructions (Thermo Fisher Scientific). Real-time PCR was performed using SYBR Green detection on a Bio-Rad CFX instrument as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
“…SIRP α binds to VEGF and immunoprecipitates with VEGFR2. CD47 antibody B6H12 downregulates VEGFR2 and SHP-2 phosphorylation [ 46 ] and CD47 binds SIRP α and TSP-1 to regulate the expression of VEGF and VEGFR2, thereby affecting the progression of atherosclerosis. Recent studies have shown that CD47 plays a role in atherosclerosis not through “cell aggregation” but through the dysregulation and activation of NK cells.…”
Section: The Influence Of Cd47 Signaling Pathway On the Formationmentioning
confidence: 99%
“…Other exosomal surface proteins such as CD47 may modulate the uptake process. For example, CD47, a thrombospondin 1 receptor, is present on the surface of EVs derived from Jurkat T cells and can alter gene expression and functional signaling in endothelial cells . Whether other microenvironmental factors modulate exosome uptake is largely unknown.…”
Section: Exosome Uptakementioning
confidence: 99%